Flight-to-safety and the risk-return trade-off: European evidence - Aslanidis, Nektarios; Christiansen, Charlotte; Savva, Christos S. (My University, 2020)
This paper investigates flight-to-safety from stocks to bonds in six European markets. We use quantile regressions to identify flight-to-safety episodes. The conditional risk-return trade-off on the stock markets is negative. Flight-to-safety episodes strengthen the negative trade-off. The effects of flight-to-safety episodes on the trade-off are qualitatively similar for own country flight-to-safety episodes, for flight from own country stock market to the US bond market, and for US flight-to-safety episodes. The strength of the trade-off is strongest for US flight-to-safety episodes. Flight-from-safety has the opposite effect on the trade-off.
Keywords: Flight-to-safety; Risk-return trade-off; European markets; Stock market; Bond market